Rhetoric Analysis of Alissa Wahid's Speech in the Webinar of Women Speak Religious Moderation on The Youtube Chanel Convey Indonesia - Nova Saha Fasadena; Rofiq Hidayat; Wardatul Jannah; Muhammad Rajief Azza (An-Nisa': Journal of Gender Studies, 2022)
This article discusses the Rhetoric Analysis of Alissa Wahid's Speech in the Women's Webinar Talking Religious Moderation on the Convey Indonesia YouTube Chanel, August 14, 2020. Alissa Wahid is the daughter of the 3rd former president of Indonesia, KH. Abdur Rahman Wahid, who called Gus Dur, is the Father of Tolerance in Indonesia and is also the coordinator of the Indonesian Gusdurian Network. It is important to analyze it because the presentation in the webinar discusses Religious Moderation and Women as Actors, and how women become actors who drive society. For this reason, researchers use descriptive qualitative methods through an interpretive paradigm. The data collection technique is watching, listening, reading, and taking notes. the analysis by interpreting the concept of persuasion and the five laws of Aristotelian rhetoric. The analytical technique used is the Miles, Huberman, and Saldana model, namely data collection, data condensation, data presentation, and leverage. The results showed that there were three persuasive rhetoric’s, those are Forensic Rhetoric, Demonstrative Rhetoric, and Deliberative Rhetoric used by Alissa Wahid. Furthermore, the findings on Alissa Wahid's speech contained a total of 41 data findings with details of 12 data from the concept of persuasive rhetoric and 15 data from the five principles of Aristotle's rhetorical law.